Patient-centered care, collaboration, communication, and coordination: a report from AMIA's 2013 Policy Meeting. Issue Volume 22:Issue e1(2015:Apr.)Special (30th August 2014) - Flatley Brennan, Patti; Valdez, Rupa; Alexander, Greg; Arora, Shifali; Bernstam, Elmer V; Edmunds, Margo; Kirienko, Nikolai; Martin, Ross D; Sim, Ida; Skiba, Diane; Rosenbloom, Trent
Abstract: In alignment with a major shift toward patient-centered care as the model for improving care in our health system, informatics is transforming patient–provider relationships and overall care delivery. AMIA's 2013 Health Policy Invitational was focused on examining existing challenges surrounding full engagement of the patient and crafting a research agenda and policy framework encouraging the use of informatics solutions to achieve this goal. The group tackled this challenge from educational, technical, and research perspectives. Recommendations include the need for consumer education regarding rights to data access, the need for consumers to access their health information in real time, and further research on effective methods to engage patients. This paper summarizes the meeting as well as the research agenda and policy recommendations prioritized among the invited experts and stakeholders.